2017
DOI: 10.14311/cej.2017.04.0032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glass Powder and Steel Slag on Properties of Concrete: A Review

Abstract: To overcome the scarcity of natural resources as construction material and to reduce the hazards from industries, industrial wastes can play a very significant role. In this paper, the influence of glass powder and steel slag is reviewed. It is concluded that glass powder and steel slag can upset some portion of concrete thereby providing significant improvement in mechanical properties of concrete consequently reducing the environmental hazards from industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The result shows that the increasing amount of milled glass enhances the workability of concrete at constant steel slag content. Previous research on the utilization of milled glass has also indicated improvement in workability with increasing content milled glass (Ali et al, 2017;Castro and Brito, 2013). This improvement may be attributed to the nonabsorbent nature as well as smooth surfaces of milled glass particles (Ali and Al-Tersawy, 2012).…”
Section: Fresh Properties Of Concretementioning
confidence: 88%
“…The result shows that the increasing amount of milled glass enhances the workability of concrete at constant steel slag content. Previous research on the utilization of milled glass has also indicated improvement in workability with increasing content milled glass (Ali et al, 2017;Castro and Brito, 2013). This improvement may be attributed to the nonabsorbent nature as well as smooth surfaces of milled glass particles (Ali and Al-Tersawy, 2012).…”
Section: Fresh Properties Of Concretementioning
confidence: 88%